E-015 Endovascular Treatment of a Ruptured Dural Arteriovenous Fistula via Direct Puncture Technique. (23rd July 2022) - Dowlati, E; Felbaum, D; Armonda, R; Mai, J; Liu, A; Sur, S
Abstract : Background: Treatments for dural arteriovenous fistulas have evolved over the last few decades with the advent of new and advanced endovascular technology. In cases where access to the fistulous point is not feasible, a direct puncture approach may be feasible and safe in the treatment of these lesions. This has been utilized in the case of carotid-cavernous sinus fistulas where access through orbital veins has allowed easier access to the fistulous point for transvenous embolization. Case Presentation: We present a technical case report of a 55-year-old female that presented with an acute parieto-occipital intraparenchymal hemorrhage. An MRI and MRA brain with and without gadolinium were obtained demonstrating a possible vascular malformation underlying the hemorrhage as well as FLAIR signal within the right pons and left medulla. ruptured dural arteriovenous fistula treated by transvenous endovascular embolization through a direct cannulation of the transverse sinus through a burrhole ( Figure ). This was done in a situation where transfemoral arterial and venous access did not allow access to the fistulous point of the lesion. After direct access via a burrhole, the patient was taken to the neurointerventional suite for direct embolization of the fistula. Right radial artery access was obtained for arterial angiogram of the left external carotid artery was completed demonstrating the dAVF. A mask was used and a lantern microcatheter over a shaped Chikai-14 microwire was advanced through the direct access vascular sheath into the venous pouch of the fistula under fluoroscopy. The microcatheter was advanced into the distal aspect of the fistula pouch in the area of the sigmoid sinus. The fistula was occluded with a combination of coils and nBCA embolic glue. The patient tolerated the procedure well and made complete recovery from her hemorrhage. She is also noted to have resolution of FLAIR signal on MRI and complete resolution of the fistula on three-month follow angiogram. Conclusion: We conclude that in cases where traditional access to the fistula is not possible, a direct cannulation is an effective method for endovascular treatment of the malformation. Disclosures: E. Dowlati: None. D. Felbaum: None. R. Armonda: None. J. Mai: None. A. Liu: None. S. Sur: None.